Analyzing Emotional Control in University Athletes: A Cross-Cultural and Gender Perspective - Abiyra, Ahmed Jabbar; Tiwari, Sandeep; Tiwari, Sandhya; Haq, Mir Ahsan Ul (Physical Education Theory and Methodology, 2025)
Background. Emotional control plays a crucial role in athletic performance and is influenced by factors such as gender and cultural context. Understanding the interplay between emotional regulation and athletic success can provide valuable insights for optimizing performance strategies. Objectives. This study aimed to investigate the role of emotional control in athletic performance among university athletes from Baghdad, Iraq, and Delhi, India, with a focus on examining differences by gender and university affiliation. It also examines the relationships between subscales of emotional control and overall performance. Materials and methods. The study involved 300 athletes aged 18 to 30 years, equally divided between Baghdad University (BU), Iraq and Delhi University (DU), India, with balanced gender representation (75 male and 75 female athletes per university). Emotional control was assessed using the Emotional Control Questionnaire (ECQ), which includes subscales for rehearsal, emotional inhibition, aggression control, and benign control. Descriptive statistics, two-way ANOVA, and Pearson’s correlations were employed for data analysis using SPSS software. Results. Emotional control scores were comparable across both universities and genders, with BU athletes scoring slightly lower (M = 34.41, SD = 5.86) than DU athletes (M = 34.66, SD = 3.46). The two-way ANOVA revealed no significant differences in overall emotional control or its subscales due to gender, university affiliation, or their interaction, except for benign control, where DU athletes scored significantly higher (F(1, 298) = 5.55, p = 0.02). Strong positive correlations were identified between overall emotional control and the subscales of benign control (r = .69, p < .01), rehearsal (r = .69, p < .01), and aggression control (r = .64, p < .01). Conclusions. The findings highlight the interrelated nature of emotional regulation components and their variable contributions to athletic performance. These insights can guide the development of training programs incorporating emotional control strategies to enhance competitive outcomes for university athletes.